REAKSI PASAR MODAL INDONESIA TERHADAP PERGANTIAN MENTERI KEUANGAN (EVENT STUDY SAHAM YANG TERDAFTAR DI BEI) - Islami, Lia Nur; Sarwoko, Endi (Jurnal Ekonomi Modernisasi, 2012)
Information is the main needs of investors in capital markets. Sri Mulyani setback Event of the positions for the finance minister who has information content relevant to investors will cause the market reaction reflected through changes in stock prices and trading activity. This reaction can be measured by indicators of Abnormal Return (AR), Trading Volume Activity (TVA) and Security Return variability (SRV). This research is a study of events that aims to find empirical evidence for the existence of the Indonesian capital market reaction to the events of Sri Mulyani setback from the office of finance minister. The population in this study is that all stocks listed on the BEI. While the sample taken through purposive sampling technique of shares - shares that are included in LQ45 corporate action and do not perform during the event period. One sample t-test (one sample t-test) was used to analyze whether the AR, TVA, and SRV significant value on the day - the day around the occurrence of events that prove the existence of market reaction. TVA and AR significant at the time of announcement of events shows that the market reacted to the setback Sri Mulyani finance minister from office. However, the SRV is not significant at the time of announcement of events shows that the market reaction that occurs there is an uneven distribution of information and influence the distribution of stock return